Ultrasonic backscatter system for automated on-line endocardial boundary detection: Evaluation by ultrafast computed tomography - Marcus, Richard H.; Bednarz, James; Coulden, Richard; Shroff, Sanjeev; Lipton, Martin; Lang, Roberto M. (Journal of the American College of Cardiology, 1993)
Objectives. The purpose of this study was to evaluate the accuracy of the recently developed echocardiographic on-line endocardial border detection system using ultrafast computed tomography, an independent and proved tomographic imaging modality. Background. The automated system for on-line endocardial border detection identifies the blood-tissue interface by acoustic quantification of the ultrasonic backscatter signal. Methods. Eighteen subjects were screened by conventional echocardiography and acoustic quantification. Ten of these, with high quality echocardiographic images, were also examined by ultrafast computed tomography. Comparable image planes at the midpapillary level were analyzed. Measurements of left ventricular cavity area were compared at end-diastole and end-systole and time course analyses of cavity area during the cardiac cycle were performed. Results. There was good correlation between values for left ventricular end-diastolic area (r = 0.99), end-systolic area (r = 0.93) and fractional area change (r = 0.91) using the two methods. The on-line backscatter system underestimated end-diastolic area (p < 0.001), but the negative bias was small (−1.6 cm2) and the 95% confidence intervals were narrow (−3.6 cm2to +0.4 cm2). In contrast, the backscatter system overestimated end-systolic area (p < 0.02); the positive bias for this variable was also small (+2.6 cm2) but the confidence intervals were relatively wide (+7.9 to −2.8 cm2). The negative bias of backscatter values for cavity area was fairly constant during diastole and early systole (range −5% to −10%), but during the second half of systole, backscatter values increased progressively relative to computed tomographic values. Real time values for fractional area change measured by the backscatter system were 13% smaller than those determined by ultrafast computed tomography (p < 0.001), with wide confidence intervals (+3% to −30%). Absolute peak rates of area change during systole and diastole were lower by 39% (p < 0.001) and 41% (p < 0.01), respectively, using the on-line ultrasonic backscatter system. Time course analyses revealed the errors to be consistent with cardiac cycle-dependent alterations in gain sensitivity of the ultrasonic backscatter system. Conclusions. The ultrasonic backscatter system is associated with cyclic cavity area measurement errors that need to be addressed if its early promise for on-line assessment of ventricular function is to be fulfilled. Incorporation of an electrocardiographically triggered time-varying gain control may improve accuracy for on-line analysis of ventricular performance.